Ectopic NORs on human chromosomes 4qter and 8q11: rare chromosomal variants detected in two families. Issue 4 (1st April 1999) - Guttenbach, M; Haaf, T; Steinlein, C; Caesar, J; Schinzel, A; Schmid, M
Abstract : Two different NOR bearing non-acrocentric chromosomes were detected during prenatal diagnosis performed on two probands because of advanced maternal age. In the first case, a chromosome 4 carried a NOR in the telomeric region of the long arm (4qs), while in the second case a NOR was inserted into chromosome 8q11. Family analysis showed the variant chromosomes to be transmitted through at least three generations in each family. There were no reports of reproductive problems or phenotypic effects in the carriers of these chromosomes, indicating the benign character of the aberrant chromosomes. In order to characterise the chromosomal variants more precisely, various differential banding techniques were applied.